EXPERIMENTAL CONSTRAINTS ON BUBBLE INTERACTIONS IN RHYOLITE MELTS: IMPLICATIONS FOR VESICLE SIZE DISTRIBUTIONS - Larsen J.F.; Gardner J.E. (My University, 2000)
We have studied interactions between bubbles of two distinct size classes in rhyolite melts experimentally decompressed between 200 and 80 MPa. The first set of `decompression' bubbles has a size range (Rdec) of 1-11 mum and is formed from nucleation and growth upon isothermal decompression of the melt. The larger populations of `hydration' bubbles are on average 30-40 mum in radius (Rhyd) and are formed from pore spaces present that were filled with water vapor during the saturation runs prior to the decompression experiments. The first type of interaction results in the elongation of decompression bubbles oriented radially around the larger hydration bubbles. The degree of elongation increases both as a function of distance and with increasing ratio of hydration to decompression bubble size (Rhyd/Rdec). The second type of interaction studied results in a reduction of the size of decompression bubbles located within a range of distances from 10 to 65 mum from a hydration bubble surface, relative to the modal size of the unaffected bubbles in the same sample. In addition, within an average distance of 10 mum, melt next to the hydration bubble surface is depleted in decompression bubbles. Our results indicate that concentration gradients in the melt are probably responsible for bubble size reduction and the depleted zones, because the predicted time scales for Ostwald ripening are much longer than those of the experiments. These effects persist even to the lowest ending pressures studied (80 MPa), which indicates that size distributions of small bubbles may be affected by concentration gradients in the depleted melt shell surrounding large bubbles. Large bubbles present in an ascending magma, prior to a subsequent nucleation event, could therefore affect the growth of the smaller bubble population occurring within the depleted melt shell of the larger bubbles, and produce a bimodal vesicle size distribution. Elongated decompression bubbles may be strained as a result of melt flowing away from the much larger hydration bubbles as they grow. Estimates of capillary number (Ca) plotted against deformation (Df) indicate that bubbles in water-rich rhyolite melts are deformable, even at small sizes (1 mum) and small values of Ca. Our results show a different trend of Df with Ca than previous studies in non-geological systems predict, indicating that viscosity effects may be important. The preservation of deformation textures depends strongly on relaxation time, explaining the lack of deformation textures in less viscous natural lavas.